Effects of combined explosive, plyometric, and sprint training on the physical fitness of soccer players - Tvrdý, M.; Holienka, M.; Lednický, A.; Kovác, K.; Mikulic, M.; Babic, M. (Journal of Physical Education and Sport, 2023)
This study aimed at investigating the efficacy of a 6-week combined plyometric and speed training program focusing on developing the speed-strength abilities of U14 soccer players. The study was conducted under the conditions of a two-group parallel experiment. Experimental groups I. and II. (EG I. and II.) consisted of youth soccer players (n = 20 and 18) in the top German and Slovak leagues, respectively. To obtain data, we performed 6 tests: squat jump (SJ), countermovement jump (CMJ), drop jump (DJ), 10-m sprint test, 20-m sprint test, and 505 agility test. EG I. players completed a 6-week experimental period, including two training sessions per week using plyometrics and short sprints, while EG II. players underwent the same experimental period without plyometrics and short sprints. Both groups completed an identical training program to develop their speed skills. Compared to the results of the EG II. group, the values of all tests were significantly more increased in the EG I. group: the SJ (p < 0.00001), CMJ (p < 0.00001), DJ (p < 0.00001), 10-m sprint test (p = 0.00122), 20-m sprint test (p = 0.00027), and 505 agility test (p = 0.00062). The results of the combined plyometric and speed program demonstrated higher efficacy in developing selected speed and strength parameters compared to the speed program without strength training. In summary, our study showed the necessity of using plyometric and sprint drills alongside game-specific training in soccer.